A preliminary study on occupational stress and job satisfaction among male navy personnel at a naval base in Lumut, Malaysia - Mohd Bokti, Nor Liyana; Abu Talib, Mansor (The Journal of International Social Research, 2009)
Job satisfaction and occupational stress both indicate workers’ appraisal towards the workplace and work itself. Thus, it is important to have valid measure of job satisfaction and occupational stress. This measure is also important in the Malaysian workplace context. A total of 40 male officers and non-officers, from the seaman and engineering and supply branch in the Lumut Naval Base participated in the study. Data were collected using a self-administered questionnaire, the Job Satisfaction Survey (Spector, 1985) and Job Related Tension Index (JRTI; Kahn et al., 1964). This preliminary study established internal consistency using Cronbach alpha values for both instruments. Additionally, the study determined the level of occupational stress, job satisfaction and relationship between occupational stress and job satisfaction facets. The findings of the study revealed that the reliability of both instruments were greater than 0.80. The majority of the male Navy personnel reported moderate levels of job satisfaction in the favorable nature of work facet. High occupational stress on the other hand, was related to an unknown superior’s evaluation of one’s workplace performance. Correlational analyses found that occupational stress was associated with overall job satisfaction and in eight of its facets. Collectively, results provide evidence that both instruments are reliable in the Malaysian military setting context. Caution should be made that findings of this preliminary study should not be generalized to the larger population due to its small sample size. A bigger sample would be needed to represent the general population.